Contralateral prefrontal and network engagement during left DLPFC 10 Hz rTMS: an interleaved TMS-fMRI study in healthy adults - van Hattem, Timo; Chang, Kai-Yen; Tik, Martin; Taylor, Paul; Björklund, Jonas; Bulubas, Lucia; Padberg, Frank; Keeser, Daniel; Campana, Mattia (NeuroImage clinical, 2025)
•Extended 10 Hz rTMS protocols with 600 stimuli can be implemented in the interleaved TMS-fMRI setting.•Left DLPFC 10 Hz rTMS predominantly engages contralateral DLPFC regions.•rTMS-induced BOLD responses extend to remote salience network nodes.•Interindividual variability in rTMS-induced BOLD responses was marked and warrants further investigation. High-frequency repetitive transcranial magnetic stimulation (rTMS) over the left dorsolateral prefrontal cortex (DLPFC) serves as an effective treatment for major depression and other psychiatric disorders. Despite its growing clinical application, the neural mechanisms by which prefrontal rTMS exerts its therapeutic effects remain incompletely understood. To address this gap, we investigated the immediate blood-oxygen-level-dependent (BOLD) activity during 600 stimuli of left DLPFC 10 Hz rTMS in healthy individuals using interleaved TMS-fMRI. In a crossover design, 17 healthy subjects received 10 Hz rTMS (60 trains with 9-second intertrain intervals) over the left DLPFC at 40 % and 80 % of their resting motor threshold (rMT) inside the MR scanner. 10 Hz rTMS over the left DLPFC elicited BOLD responses in prefrontal regions, cingulate cortex, insula, striatum, thalamus, as well as auditory and somatosensory areas. Notably, our findings revealed that 10 Hz rTMS effects were lateralized towards the contralateral (right) DLPFC. Dose-response effects between 40 % vs. 80 % rMT were exclusively observed in the hippocampus. The 10 Hz rTMS protocol used in this study induced distinct target engagement and propagation patterns in the prefrontal cortex. These patterns differ from our previous interleaved TMS-fMRI findings using 600 stimuli of left DLPFC intermittent theta burst stimulation (iTBS) at the same intensities. Thus, interleaved TMS-fMRI emerges as a valuable method for comparing clinical prefrontal rTMS protocols regarding their immediate effect on brain circuits in order to differentiate their action mechanisms and to potentially inform clinical applications.